Differences in Public Perceptions and Leaders' Perceptions on Hydraulic Fracturing and Shale Development. (September 2015) - Crowe, Jessica; Silva, Tony; Ceresola, Ryan G.; Buday, Amanda; Leonard, Charles
New technologies and rising energy prices have resulted in many energy companies investing significant amounts of capital in rural America. Much of the recent focus of energy companies has been on the development of shale oil and natural gas. We examine the differences in levels of support and opposition to shale oil and gas development, building on the literatures of the growth-machine coalition, polluter-industrial complex, and environmental justice. Specifically, we examine different frames of shale development held by government leaders and the public who reside above the New Albany shale play in Southern Illinois and Northwest Kentucky. Using a combination of interview, survey, and participant observation data, we find that government officials emphasize economic growth and many support shale development. While most government leaders claimed that there was not a major division in their communities about shale development, we found the public to be split, with a large countercoalition to shale development in existence.